Aiol : a chanson de geste - Malicote, Sandra; Hartman, A. Richard, 1939- (Medieval and Renaissance texts (New York, N.Y.), 2014)
This first English translation of the chanson de geste, Aiol, records the exploits of the epoymous young knight as he reclaims his parent's unjustly stolen heritage. He gains the love of a Saracen princess who converts, convinced of the truth of the Christian god by Aiol's prowess. He aids the French King Louis in ending a debilitating war led by rebellious vassals and (in an allusion to the Fourth Crusade) helps Emperor Grasien, the king of Venice, end his own war against an enemy to the East. Aiol's deeds bring justice to France. But the poem is far more than the tale itself. Aiol, like many.